2014
DOI: 10.1021/ma501853c
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Microcapsules Based on Multilayer Assembly of Star Polyelectrolytes

Abstract: Star polyelectrolytes (poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA)) with dual (temperature and pH) responsive properties were utilized to fabricate multiresponsive microcapsules via layer-by-layer (LbL) assembly. The LbL microcapsules are very robust and uniform, with higher stability and different internal structure compared with conventional microcapsules based on linear polyelectrolytes. Ionic strength in the polyelectrolyte solution during the microcapsule assembly process has a significant influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 69 publications
0
47
0
Order By: Relevance
“…98 Star polymers have also been used as components to fabricate thin-shell microcapsules. 101 The fabricated microstructures possess complex internal structures and unique stimuli-responsive behavior.…”
Section: Assembly Of Star Polyelectrolytesmentioning
confidence: 99%
“…98 Star polymers have also been used as components to fabricate thin-shell microcapsules. 101 The fabricated microstructures possess complex internal structures and unique stimuli-responsive behavior.…”
Section: Assembly Of Star Polyelectrolytesmentioning
confidence: 99%
“…Based on the multilayer assembly of star polyelectrolytes (PDMAEMA) with dual‐responsive (temperature and pH) properties, Tsukruk and co‐workers designed and synthesized multi‐stimuli‐responsive microcapsules with higher stability and different internal structure compared with conventional microcapsules based on linear polyelectrolytes. They demonstrated that with increasing pH, the permeability of the multi‐responsive microcapsules decreased; the overall size and permeability of the multi‐responsive microcapsules decreased with increasing temperature 196…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…3d. 45,59 Hence, the rough surface created by ZIF-8 nanotemplates endowed Z-TiO 2 MCs with high mechanical strength, thus preserving the spherical shape upon drying. 27,29 Z-TiO 2 MCs were obtained after removing CaCO 3 and ZIF-8 dual templates.…”
Section: Preparation and Characterization Of Z-tio 2 Microcapsulesmentioning
confidence: 99%